Implementation challenges of the 9-year basic education curriculum in Nigeria:implications for planning, policy and law (2012)
This study investigated implementation challenges of the new 9-year Basic Education Curriculum in Nigeri-a.Three hundred and fifty one primary school teachers that were selected from all the Local Government Areas of Osun State were used for the study. They provided information on the availability and quality of teachers for the newly introduced subjects at the primary school level. Curriculum Implementation Questionnaire [CIQ] was used to generate data for the study. The Cronbach alpha reliability coefficient estimated on CIQ was 0.65. Descriptive statistics was adopted to analyse the data. It was found that majority of primary school teachers in the state have the Nigeria Certificate in Education [NCE] as their minimum qualification, and majority of them had taught for more than ten years. Majority of the sampled teachers were not aware of the introduction of Computer Studies, Civic Education and Life Skills. They also indicated that there were no teachers for the newly introduced subjects [Basic Science and Technology, Computer Studies, Civic Education and Life Skills in their schools. The findings of this study clearly revealed complete lack of the required subject teachers in most schools. In order for the implementation of the new curriculum to achieve the desired success, there is an urgent need to adopt some planning, policy and legal measures.